Ideologia em Ernesto Laclau - Ferreira, Henrique Amaral (2022)
The present work analyzes the deflation of the relevance of the term ideology in Ernesto Laclau's work and its subsequent reincorporation into the author's theoretical body. The work is developed from two axes, which guide two traditional conceptions of ideology in Marxist theory: as a level of social totality and as a false consciousness. Our exploration leads us to the elaboration of the way in which Laclau deals with the discursive construction of the totality of the political community and of individual subjectivity, from a matrix of criticism of the Marxist theory of ideology.